TRANSFORMATION OF THE DRUG MONITORING SYSTEM THROUGH LEAN SIX SIGMA (LSS) - Mojaza Sirait; Ratih Hendayani (International Journal Management and Economic, 2025)
Drug distribution oversight in Indonesia faces recurring violations, weak regulatory enforcement, and inefficiencies in post-inspection follow-ups. This study investigates the root causes of these issues and evaluates the effectiveness of Lean Six Sigma (LSS) in improving the supervision system at the Indonesian Food and Drug Authority Regional Office in Serang. A qualitative approach using the DMAIC (Define, Measure, Analyze, Improve, Control) framework was applied to analyze inspection reports, institutional performance data (2019–2024), and in-depth interviews with key stakeholders. The findings reveal that repeated violations stem from ineffective CAPA processes, limited human resource capacity, fragmented regulations, and the absence of integrated digital systems. Implementing LSS led to faster follow-up actions, standardization of inspection procedures, and improved coordination. The study concludes that LSS can serve as a strategic method to enhance data-driven, collaborative, and risk-based drug surveillance. This research contributes to the development of digital public health supervision models and highlights the need for regulatory harmonization across institutions